MENTAL HEALTH IN THE SOCIAL AND PSYCHOLOGICAL CONTEXT: ADDRESSING THE CHANGES FACED BY ADOLESCENTS IN THE MODERN ERA: A Literature Review - Ghulam Haikal Adn; Verawaty, Liana (Journal of Diverse Medical Research: Medicosphere, 2025)
Adolescent mental health is a crucial aspect influenced by various psychosocial, emotional, and social factors. Changes in the lives of adolescents, such as the impact of social media, social pressure, and technological developments, can worsen their mental health conditions. The COVID-19 pandemic further exacerbated this situation, with many adolescents experiencing anxiety, depression, and stress due to social restrictions and school closures. In addition, social stigma and a lack of understanding about mental health often create barriers to seeking help. Studies show that factors like positive interactions with family and peers can help reduce psychological symptoms, while a family's socioeconomic status also plays a role in adolescent mental health. This article examines the various factors affecting adolescent mental health and highlights the importance of family involvement and evidence-based interventions to support their psychological well- Methode : This research employs a literature analysis approach by reviewing relevant theoretical and empirical sources, including Google Scholar, PubMed, and Science Direct. Conclusion : Adolescent mental health is influenced by psychosocial, socio-economic, and technological factors, particularly during the COVID-19 pandemic. Anxiety, depression, and stress have increased, with stigma and a lack of mental health awareness exacerbating these conditions. Positive interactions with family and peers, as well as a family's socio-economic status, play a crucial role in supporting adolescent mental health. Efforts to improve mental health literacy, reduce stigma, and strengthen social support are essential for prevention and intervention.